Strategi Muamalah Atasi Inflasi Di Desa Manunggal, Deli Serdang - Putra, Muhammad Umar Maya; Damanik, Syafrida; Sinto, Sinto; Sari Nasution, Asmara (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Tjut Nyak Dhien, 2025)
This community service aims to integrate Fiqh Muamalah Amaliyah based on Maqashid Sharia in addressing inflation as a contemporary economic challenge that affects public welfare. High inflation reduces purchasing power and widens social inequality. Therefore, fiqh muamalah, grounded in Islamic values such as justice (al-‘adl), public benefit (al-maslahah), and protection of wealth (hifzh al-mal), is used as a normative and applicative approach. The program was implemented in Manunggal Village, Deli Serdang, involving women from the Family Welfare Movement (PKK) through three stages: preparation, implementation, and evaluation. The service earning methods included interactive lectures, literature study, group discussions, and SWOT analysis to understand the potential and challenges of household businesses. The results showed improved participants’ understanding of Islamic economic principles, the emergence of new business ideas based on Islamic ethics, and the development of practical guidelines for dealing with inflation. Evaluation was conducted through pre-tests, post-tests, and participatory observation, indicating the effectiveness of this approach in fostering Islamic economic awareness at the grassroots level. This community service highlights the importance of fiqh muamalah as an adaptive and contextual solution to local economic dynamics, while also promoting sustainable family economic empowerment.